Gonadotropin-releasing hormone II: a multi-purpose neuropeptide - Schneider, Johanna S. (Integr Comp Biol, 2008)
Close to 30 forms of gonadotropin releasing hormone (GnRH) and at least five GnRH receptors have been identified in a wide variety of vertebrates and some invertebrates. One form, now called GnRH II, has the broadest distribution and the most ancient and conserved phylogeny. The distribution of the neurons that produce this peptide are completely nonoverlapping with any other GnRH forms. Fibers that project from these neurons overlap with GnRH I cells and/or fibers in a few regions, but are primarily divergent. The musk shrew (Suncus murinus) continues to be the most tractable mammalian species to use for studies of the function of GnRH II. The brain of the musk shrew has two GnRH genes (I and II), two GnRH receptors (types-1 and -2), and two different behaviors can be influenced by central infusion of GnRH II, but not by GnRH I; receptivity and feeding. Here, we summarize research on the musk shrew relative to the behavioral functions of GnRH II. First, female musk shrews are continually sexually receptive by virtue of their lack of an ovarian and/or behavioral estrus cycle. This feature of their reproductive ecology may be related to their semi-tropical distribution and their breeding season is highly dependent on changes in the availability of food. When food is not abundant, females stop mating, but brief bouts of feeding reinstate reproductive behavior. Likewise, intake of food is related to GnRH II mRNA and peptide content in the brain; after mild food restriction both decline. When GnRH II is infused centrally, at times when its content is low, it can both enhance receptivity and inhibit food intake. Simultaneous administration of a type-1 antagonist does not change the effect of GnRH II and use of an analog (135-18) that is a specific GnRH II agonist as well as a type-1 antagonist has the same effect as the endogenous GnRH II peptide. We propose that GnRH II plays a critical role by orchestrating the coordination of reproduction with the availability of nutritional support for these activities. Humans are bombarded with copious nutritional opportunities and at present obesity is a larger threat to health in many parts of the world than is under nutrition. It is our hope that understanding neuropeptides such as GnRH II that regulate food intake can ultimately lead to products that may curb appetite and thus decrease obesity and related risks to health.